Effects of resistance training cessation on cycling performance in well-trained cyclists: an exploratory study - Bláfoss, R.; Rikardo, J.; Andersen, A. Ø.; Hvid, L. G.; Andersen, L. L.; Jensen, K.; Christensen, P. M.; Kvorning, T.; Aagaard, P. (The Journal of Strength and Conditioning Research, 2022)
Supplementary (i.e., concurrent) resistance training can enhance cycling performance among competitive cyclists. However, a lack of knowledge exists about the retention (decay profile) in mechanical muscle function and cycling performance after concurrent resistance and endurance training. The present exploratory intervention study investigated the effect of 6 weeks of resistance training cessation when preceded by 8 weeks of concurrent resistance and endurance training on mechanical muscle function and cycling performance in 9 male well-trained competitive cyclists (Vo2max = 66 ± 7 ml/min/kg). Cyclists performed periodized resistance training targeting leg and core muscles for 8 weeks as a supplement to their normal endurance (cycling) training. This was followed by 6 weeks of endurance training only (retention period) leading up to the start of the competitive season. Maximal leg extensor power, isometric leg extensor strength (maximal voluntary contraction [MVC]), rate of force development (RFD), and long-term cycling performance (2-hour submaximal cycling at 55% of Wmax), followed by 5-minute max cycling were evaluated. After 8 weeks of concurrent resistance and endurance training, leg extensor power, MVC, and RFD increased by 12, 15, and 17%, respectively while mean power output (W) during 5-minute max cycling increased by 7% (p < 0.05). Training-induced gains in MVC and 5-minute max cycling power were retained after 6-week cessation of resistance training (p < 0.05). These findings indicate that competitive cyclists can focus on cycling training alone for at least 6 weeks leading up to competition without losing attained gains in maximal muscle strength and cycling performance achieved by preceding periods of concurrent resistance training.